Dissecting logical statements in EFL undergraduate thesis abstracts: Gaining insight through cohesive and coherent mechanisms - Ginting, Pirman; Sulistya Ningsih Pratiwi; Ika Agustina; Yenni Hasnah; Rosmen, Rosmen (English Language Teaching Educational Journal, 2026)
A well-structured composition must be both coherent and cohesive, enabling arguments to flow logically and ensuring clarity for readers. Yet, this critical aspect of academic writing is often overlooked, particularly in the thesis abstracts of EFL college students. Thus, this study investigates how cohesive and coherent mechanisms are employed to construct logical arguments in student-written thesis abstracts. By applying qualitative content analysis, the research examined patterns of cohesive ties and their contribution to overall textual coherence. The data employed for this research were ten theses abstracts accessed publicly from the universities’ official repositories.  The findings indicate that cohesive devices play a crucial role in shaping coherence, with greater cohesion typically resulting in stronger logical connections within the text. Transition markers, which establish semantic links between clauses and sentences, emerged as the most influential indicators of coherence. These markers guided readers through the arguments and ensured a more unified presentation of ideas. The results suggest that the effective use of cohesive and coherent strategies not only improves the clarity of thesis abstracts but also enhances their academic quality. This highlights the pedagogical need to integrate explicit instruction on cohesion and coherence into EFL writing courses. By fostering students’ awareness and mastery of these devices, educators can support the development of more precise, persuasive, and professional academic writing. Ultimately, improving these skills can raise the standard of student theses and contribute to higher levels of scholarly communication.